Nations with high smoking rate have low SARS-CoV-2 infection and low COVID-19 mortality rate - Landoni, Giovanni; Zangrillo, Alberto; Romero García, Carolina Soledad; Faustini, Carolina; Di Piazza, Martina; Conte, Francesca; Gattarello, Simone; Kuzovlev , Artem; Likhvantsev , Valery; Puglisi, Riccardo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work The effect of tobacco smoking on COVID-19 disease is debated with common sense and experts suggesting a deleterious effect and manuscripts worldwide reporting a low prevalence of active tobacco smokers among intensive care unit patients. Methods We categorized countries worldwide into three groups with <25%; 25-45%; >45% of active male smokers with data expressed as median and interquartile range [IQR] and extracted data on SARS-CoV-2 infections and COVID-19 deaths per million inhabitants. We also applied multivariate regression techniques to adjust for several epidemiological factors. Results COVID-19 mortality was 13 (5-24) per million inhabitants in countries with male smokers >45% and 33 (4-133) in countries where male smokers were <25%. SARS-CoV-2 infection rates were 436 (217-954) and 1139 (302-4084) with data confirmed when dividing data for each continent and when controlling for confounding factors. Conclusions We found a counterintuitive low COVID-19 mortality and SARS-CoV-2 infection in countries with high prevalence of male smokers at the global level and within each continent, suggesting that active smoking habit is protective. Further research should urgently investigate which is the possible mechanism of action.